Fc-Mediated Functions of Porcine IgG Subclasses - Paudyal, Basudev; Mwangi, William; Rijal, Pramila; Schwartz, John C.; Noble, Alistair; Shaw, Andrew; Sealy, Joshua E.; Bonnet-Di Placido, Marie; Graham, Simon P.; Townsend, Alain; Hammond, John A.; Tchilian, Elma (Frontiers in Immunology, 2022)
The pig is an important agricultural species and powerful biomedical model. We have established the pig, a large natural host animal for influenza with many physiological similarities to humans, as a robust model for testing the therapeutic potential of monoclonal antibodies. Antibodies provide protection through neutralization and recruitment of innate effector functions through the Fc domain. However very little is known about the Fc-mediated functions of porcine IgG subclasses. We have generated 8 subclasses of two porcine monoclonal anti influenza hemagglutinin antibodies. We characterized their ability to activate complement, trigger cytotoxicity and phagocytosis by immune cells and assayed their binding to monocytes, macrophages, and natural killer cells. We show that IgG1, IgG2a, IgG2b, IgG2c and IgG4 bind well to targeted cell types and mediate complement mediated cellular cytotoxicity (CDCC), antibody dependent cellular cytotoxicity (ADCC) and antibody mediated cell phagocytosis (ADCP). IgG5b and IgG5c exhibited weak binding and variable and poor functional activity. Immune complexes of porcine IgG3 did not show any Fc-mediated functions except for binding to monocytes and macrophages and weak binding to NK cells. Interestingly, functionally similar porcine IgG subclasses clustered together in the genome. These novel findings will enhance the utility of the pig model for investigation of therapeutic antibodies